2023
DOI: 10.3390/ijms24076621
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Curcumin and Piperine Effects on Glucose Metabolism: The Case of an Insulinoma Patient’s Loss of Consciousness

Abstract: The hypoglycemic properties of curcumin supplements in therapeutic doses are well-known and may represent a useful tool for the treatment of chronic diseases such as metabolic syndrome, insulin resistance and type 2 diabetes. The poor bioavailability of curcumin can be improved with the concomitant administration of piperine, with no severe adverse effects on glycemia reported so far in the literature. In this article, we further discuss a previously reported case of a helicopter pilot, affected by grade I obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
0
7
0
1
Order By: Relevance
“…These three have been shown to exert anti-inflammatory and antioxidant effects, amongst other beneficial biological activities, including antitumoral, neuroprotective, antimicrobial, hepatoprotective and antirheumatic activities. 27 T2DM patients with poor glycemic control can be characterized by their constant hyperglycemic state. The constant and chronic hyperglycemic state contributes to the production of Advanced Glycation End products (AGEs) and Reactive Oxidative Species (ROS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These three have been shown to exert anti-inflammatory and antioxidant effects, amongst other beneficial biological activities, including antitumoral, neuroprotective, antimicrobial, hepatoprotective and antirheumatic activities. 27 T2DM patients with poor glycemic control can be characterized by their constant hyperglycemic state. The constant and chronic hyperglycemic state contributes to the production of Advanced Glycation End products (AGEs) and Reactive Oxidative Species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…The main constituents of curcumin are curcumin I (1,7-bis(4-hydroxy-3-methoxyphenyl) -1,6-heptadiene-3,5-dione), curcumin II (demethoxycurcumin) and curcumin III (bisdemethoxycurcumin). 27 The three types of curcumin constituents differ in their aromatic rings. These three have been shown to exert anti-inflammatory and antioxidant effects, amongst other beneficial biological activities, including antitumoral, neuroprotective, antimicrobial, hepatoprotective and antirheumatic activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A natural compound that has attracted the interest of researchers is curcumin, a polyphenol extracted from the rhizome of Curcuma longa L. A consistent piece of evidence has demonstrated that it has different pharmacological properties, including anti-inflammatory, antioxidant, neuroprotective and anti-tumoral effects [ 36 ], and it is also able to improve glucose and lipid metabolism [ 37 ]. However, the potential therapeutic application of this molecule is strongly limited by its scarce bioavailability as a consequence of its low solubility in water and rapid clearance [ 38 ]. Combinatorial treatments aimed at improving both curcumin bioavailability and its half-life have identified piperine, an alkaloid extracted by Piper nigrum L. and Piper longum , as a possible candidate to be co-administered with curcumin.…”
mentioning
confidence: 99%
“…However, in a recent case study, Servida et al demonstrated that this combination treatment should be better explored. Indeed, in a patient exposed to a low-altitude condition, curcumin/piperine co-administration induced severe hypoglycemia followed by a transient loss of consciousness [ 38 ].…”
mentioning
confidence: 99%